EFISIENSI DAN KESINAMBUNGAN FINANSIAL LEMBAGA KREDIT MIKRO NON BANK - Ashar, Khusnul (Journal of Indonesian Applied Economics, 2008)
This study aims to know the degree of efficiency and continuity of non-bank microcredit financial institution (MFIs). In average when the number of members reaching1200 people. This project is at break-even point (BEP). Also found that with as manyas 2000 members and the range of loan around 150 thousand rupiahs to USD 175thousand rupiahs, the project can cover 85% of total costs  including the  imputedcost. Level of ability of this institution is largely determined by the quality of humanresources involved in this activity; both the level of human resources at Head Officeor  in  the member  level. To  foster and  develop  poverty  community  business,  theappropruate institute  character is not bureaucratic, flexible, bottom-up, independent,has a pattern of clear planning and evaluation and has the ability to build a mentalattitude of small entrepreneurs to  success entrepreneurs.Keywords: financing, non-bank credit institutions, efficiency